Unilateral neglect syndrome clinical and topographic study of 20 subjects - Luciano Ribeiro Pinto Jr.; Sylvio Saraiva; Wilson Luiz Sanvito (Arquivos de Neuro-Psiquiatria)
Twenty patients with unilateral neglect syndrome were studied. They were 10 males and 10 females, and they ranged from 29 to 76 years of age. All were submitted to a CAT scan of the brain. Based on the findings in our sample we drew the following conclusions: the extinction phenomenon was a constant manifestation of unilateral neglect; the line crossing test proved to be most efficient for the identification of visual neglect; the right parietal lobe was the anatomical region most often involved in the unilateral neglect syndrome.